Synthesis and characterization of MEL and FAU zeolites doped with transition metals for their application to the fine chemistry under microwave irradiation - Azzolina Jury, Federico (2012)
Doped zeolites with transition metals were prepared for their application to the synthesis of chemical compounds under microwave irradiation. The zeolite crystalline structures were verified by XRD. Their surface areas were determined by the BET method. Lewis and Brönsted acid sites were quantified by FTIR of adsorbed pyridine in zeolites. The characterization of acidic properties revealed the generation of new Lewis acid sites after transition metal incorporation into zeolites. The dielectric properties of compacted zeolites were measured by using a reflection method. The temperature profiles of these compacted beds were measured during heating under microwave irradiation. Heating phenomena in zeolites were interpreted using a modified Debye model. Two main dielectric mechanisms were determined in zeolites: rotational polarization phenomenon and interfacial polarization. The selective catalytic oxidation of styrene with hydrogen peroxide was studied over zeolites doped with transition metals in a batch system, under conventional and microwave heating. Benzaldehyde was the main product in all the samples under study. Styrene conversion showed an important influence of the transition metal nature and content and so, the kind of zeolite structure used. With the present experimental conditions, no difference was proved between microwave and conventional heating neither on activity nor on selectivity.